PO061 Spontaneous vertebral artery dissection presenting as hemicrania continua-like headache. (1st December 2017) - Bonello, Michael; Mills, Samantha J; Fratalia, Lauren
Abstract : Objective: To report a patient who presented with acute symptoms resembling hemicrania continua, in whom further investigations demonstrated an acute ipsilateral vertebral artery dissection. Results: A 30-year-old female patient presented with a seven-day history of worsening left sided headaches focused in the orbit, with ipsilateral ptosis and eyelid oedema. She also reported severe neck pain ongoing for two weeks, with no traumatic precipitant. A CT angiogram showed an extracranial left vertebral artery dissection with flow occlusion, and an MRI confirmed a mural thrombus. There was no evidence for acute brain ischaemia. The patient's symptoms persisted for several months and partially responded to a left greater occipital nerve block. Conclusion: The co-occurrence of vertebral artery dissection and trigeminal autonomic-type headache is very rare.We have not identified any previous reports of vertebral artery dissection presenting with features of hemicrania continua.